To factor that out,
you should transform that first into standard form.
ax² + bx + c
then locate the three numbers. (a,b,& c)
That would be -10x²+11x+6 (always put in detail their signs)
a = -10
b = 11
c = 6
And then, two start off, you have to find ac
meaning, the product of "a" and "c" and that would be??
I'll wait for your reply, let's answer it together.
ac = -60
then find the factors of -60, which when added together becomes b.
Let's say the factors are
-4, & 15
-15, & 4
then add them together...
-15 + 4 = -11
-4 + 15 = 11 "Ding! we have a winner!"
btw we can also look at it as, 15 +(-4) = 11 or 15-4 = 11
So now we can say that
15x - 4x = 11x now substitute the factors into the equation
-10x² +15x - 4x + 6 group the 2 terms on the left, and the 2 terms on the right.
(-10x² +15x)+(-4x+6) and then simply factor out both.
-5x( 2x - 3) + (-2)(2x - 3)
-5x( 2x-3) -2(2x - 3) simplify the common multiple, "(2x-3)"
I believe we're done. I hope it was clear, this is like my first serious answer. :D